The year without Christmas - Suzanne, Jamie; Pascal, Francine; Copyright Paperback Collection (Library of Congress) (New York : Bantam Books, 1997)
Jessica and Elizabeth Wakefield couldn't be more excited about their Christmas Eve tree-trimming party, but when Jessica tries to hog all the attention at the party, she ends up destroying the Christmas tree, ruining Elizabeth's evening, and making a total fool of herself.
RL 4.
Keywords: Christmas stories; Twins -- Fiction; Young adult fiction